Functional activity of gdТ-cells in atopic dermatitis - Ye. G. Chourina; V. V. Klimov (Бюллетень сибирской медицины)
Functional activity of gdТ-cells in atopic dermatitis (AD) in dependence on the disease stage and concomitant pathology character was studied. We investigated 86 patients: 54 women and 32 men aged 17—50 years. AD patients revealed significant insufficiency of the cell immunity, the most marked of them being in gdТ-cells.The level of CD8aa did not differ practically but number of CD8ab-cells and NK-cells was decreased. Clinically, it manifested in continuously recurrent course of the disease with high risk of complications with joiningbacterial and viral infections.